Are patients benefiting from participation in the German skin cancer screening programme? A large cohort study based on administrative data. (1st January 2022) - Datzmann, T.; Schoffer, O.; Meier, F.; Seidler, A.; Schmitt, J.
Summary: Background The German programme for skin cancer screening was established in 2008 with the aim of reducing skin cancer mortality. However, the effectiveness and risk–benefit ratio of the programme remain unclear. Objectives To compare the mortality rates of patients with melanoma who participate in a screening programme to those who do not. Methods A retrospective cohort study, based on pseudonymized health insurance data of 1 431 327 individuals from Saxony, Germany, was conducted for the period 2010–2016. Patients with prevalent and incident melanoma were defined based on diagnosis, medical procedures and prescriptions. Patients who underwent screening and had a first diagnosis of melanoma within 2 years of screening were assigned to the intervention group. Relative survival and Cox regression were used to assess potential differences in mortality. Results We identified 4552 individuals with prevalent and 2475 individuals with incident melanoma. The percentage of screening participants ( n = 1801) who had locoregional (4·2% vs. 13·5%) and/or distant metastases (4·3% vs. 8·0%), or who were treated with systemic anticancer therapies (11·6% vs. 21·8%) was lower vs. nonparticipants ( n = 674). Screening participants had significantly better survival rates. The unadjusted Cox model gave a hazard ratio (HR) of 0·37 [95% confidence interval (CI) 0·30–0·46]. After adjusting for named confounders, the effect remained (HR 0·62, 95% CI 0·48–0·80). Conclusions Patients who participated in the screening programme had lower mortality than those who had not undergone screening. However, these findings may result from a healthy screen bias and/or overdiagnosis associated with screening, and not from the screening itself.